GAMBARAN KEJADIAN PENYAKIT PERIODONTAL PADA USIA DEWASA MUDA (15-30 TAHUN) DI PUSKESMAS SRONDOL KOTA SEMARANG - Wahyu Estining Tyas; Henry Setyawan Susanto; Mateus Sakundarno Adi; Ari Udiyono (Jurnal Kesehatan Masyarakat (Undip), 2016)
Periodontal diseases are mainly the results of infections and inflammation of the gums and bone that surround and support the teeth. The prevalence of periodontal disease in the world is more than 82% in young people and more than 50% in adults. The purpose of this study to describe the prevalency periodontal disease in young people (15-30 years). This study was an analytic with cross sectional design. This study is conducted in Srondol Primary Health Center Semarang in June-July 2016. Thereby, the study uses analytic research with cross sectional design conducted in Srondol Primary Health Center Semarang in June-July 2016. The sampling technique is consecutive sampling. Out of the 95 respondents, the study found 45,3% respondents are with periodontal disease. The advice given is to improve education through demonstration and practice about dental and oral disease prevention, especially the quality of the toothbrush in small groups in community organizations.